Leverage, liquidity, and working capital efficiency affect manufacturing companies' profitability on the IDX - Putu Nuniek Hutnaleontina; Kadek Dewi Padnyawati; I Gusti Ayu Tri Cintya Dewi (Institute of Computer Science (IOCS), 2023)
The development of manufacturing companies in Indonesia is currently ongoing. However, many businesses still have profitability issues due to poor asset management. This affects a company's leverage, liquidity, and working capital. This study analyzes the role of leverage, liquidity, and working capital efficiency in influencing manufacturing companies' profitability on the Indonesian stock exchange (IDX). Quantitative research utilizing secondary data obtained from the IDX related to companies engaged in manufacturing. The total sampling technique, which included 500 companies, determined the research sample. The data were analyzed using multiple linear regression. Profitability is an essential aspect of a company's ability to obtain expected results. Various predictors affect profitability, including leverage, liquidity, and working capital efficiency. The findings show that leverage, liquidity, and working capital effectiveness can affect profitability by 9% with a probability of 0.000 (p<0.05). The equation is Y= -2.861+ 0.459 X1 -0.218X2 + 0.304X3 + e. As a result, leverage and working capital efficiency can positively and significantly affect profitability but not liquidity.